Features of iron homeostasis in patients with steatohepatitis of alcoholic and non-alcoholic etiology and its correlation with the intensity of oxidative stress and apoptosis - O. S. Khukhlina; T. M. Antofiichuk; M. P. Antofiichuk (Kazimierz Wielki University, 2021)
Topicality. Comorbid course of alcoholic steatohepatitis (ASH) and non alcoholic steatohepatitis (NASH) with dysmetabolic iron overload syndrome (DIOS) is caused by the cascade of interload reactions, which may contribute to the progression of the disease. DIOS is a pathological condition characterized by a quantitative increase in the content of elemental iron in the body, which leads to the damage of organs and tissues due to the toxic effects of excess iron. DIOS formation is associated with congenital or acquired insufficiency of mechanisms of the regulation of iron excretion, accumulation in the population of gene mutations of proteins-regulators of iron metabolism; inefficient erythropoiesis and insufficient utilization of iron in the bone marrow, with the changes in the quality of nutrition (predominant consumption of meat products); increasing life expectancy, living in geozones with high iron content in water bodies, soils, associated both with natural features and industrial production. Other risk factors leading to the development of DIOS include multiple blood transfusions, unreasonable, uncontrolled prescription of iron-containing drugs, alcohol abuse, tobacco smoking, obesity, diabetes mellitus (DM), hormone replacement therapy with steroid hormones and estrogens, and more. The aim of the work is to establish the features of iron homeostasis in patients with steatohepatitis of alcoholic and nonalcoholic etiology, to identify the dependence of steatohepatitis, oxidative-antioxidant homeostasis and the intensity of hepatocyte apoptosis on the presence of iron overload syndrome. Materials and methods. 125 patients were examined, including 60 patients with NASH and 65 patients with ASH, 25 practically healthy persons of the corresponding age and sex. Among the examined patients with NASH, there were 15 male patients (25.0%) and 45 female patients (75.0%). The mean age of the examined patients was (46.3 ± 5.2) years. Among the examined patients with ASH there were 56 male patients (86.2%) and 9 female patients (13.8%). The mean age of patients with ASH was (47.4 ± 5.1) years. The control group consisted of 25 healthy individuals (PHIs), namely male - 11 (44.0%) and female - 14 (56%). The mean age of PHIs was (41.3 ± 2.1) years. The diagnosis of NASH and ASH was established according to the unified clinical protocol approved by the order of the Ministry of Health of Ukraine № 826 from 06.11.2014, in the presence of the criteria for excluding the possibility of chronic diffuse liver disease of viral, hereditary, autoimmune or drug genesis being a cause of cytolytic, cholendoma-cholestatic-melestatic , as well as the results of ultrasonography of the liver with shear wave elastography, Steato-test, ASH-test, NASH-test (BioRedictive, France). Results. The frequency of clinical syndromes in NASH varied depending on the presence of DIOS as follows: under DIOS conditions the frequency of cholestatic syndrome prevailed (3.1 times, p <0.05), abdominal discomfort in the right hypochondrium (3.5 times, p <0 , 05), the incidence of splenomegaly (7.0 times, p <0,05). The analysis of biochemical syndromes in patients with ASH depending on the presence of DIOS indicates a significantly higher incidence of cholestasis (2.7 times, p <0.05), hepatocellular insufficiency (4.3 times, p <0.05), as well as impaired glucose tolerance (2.8 times, p <0.05) in patients with DIOS compared with the incidence of these syndromes in ASH without DIOS. The analysis of the biochemical parameters of ferrokinetics indicates a probable increase in serum iron in patients with NASH with DIOS - 1.7 times (p <0.05) compared with PHIs, and in the absence of DIOS- iron content corresponded to the reference values (p> 0.05). The course of ASH is accompanied by a manifest DIOS in 61.5% of patients, also accompanied by hypersideremia, hyperferritinemia, hypertransferinemia and a significant increase in the percentage of TS (in the range of 1.7-4.3 times), which causes increased activity of cytolytic syndrome compared to ASH without DIOS. A strong correlation was found between the content of iron in the blood and the activity of AST (r = 0.61, p <0.05), the content of transferrin in the blood and AST (r = 0.67, p <0.05), the content of blood ferritin and AST (r = 0.75, p <0.05) in patients in this group. At the same time, patients with ASH without DIOS are also characterized by, but less intense (within 1.3-1.6 times), an increase in blood iron, ferritin and transferrin, the percentage of TS, which confirms the opinion of scientists that the indicators of ferrokinetics should be used as a significant diagnostic criterion for ASH. Among the patients with NASH on the background of obesity, the manifestation of DIOS was registered in 30.0% of patients with hypersideremia, hyperferritinemia, hypertransferinemia, the increase in the percentage of TS (within 1.5-2.7 times). The course of NASH without DIOS was characterized by hyperferritinemia (p <0.05), which can be regarded as a marker of active mesenchymal inflammation. Conclusions. 1. The course of ASH is accompanied by a manifest iron overload syndrome in 61.5% of patients, which is accompanied by hypersideremia, hyperferritinemia, hypertransferrinemia and a significant increase in the percentage of iron transferrin saturation, which causes increased activity of cytolytic syndrome without comparison.2. In patients with NASH on the background of obesity, the manifestation of DIOS was registered in 30.0% of cases, in which hypersideremia, hyperferritinemia, hypertransferrinemia, increase in the percentage of TS, which can be regarded as a marker of inflammatory activity. 3. The course of alcoholic and non-alcoholic steatohepatitis is accompanied by significant oxidative stress, which increases with the accession of DIOS. 4. The main signs of disintegration of the parameters of the antiradical defense system in patients are compensatory, in response to the activation of oxidative stress and endotoxicosis, increased glutathione peroxidase activity and progressive decrease in erythrocytes of reduced glutathione, the depot of which is depleted in proportion to intensity. 5. The presence of DIOS significantly enhances the intensity of hepatocyte apoptosis.